Shine : rediscovering your energy, happiness & purpose - Cope, Andrew, 1966-; Oattes, Gavin, 1979- (John Wiley & Sons, 2018)
Start living the life you've always wanted It could be that you've figured everything out on your own and have ended up acing your career, meeting and marrying your perfect partner, producing three wonderful kids, owning a holiday home in Mustique and having a drop-dead gorgeous life. In which case, we applaud you. If, on the other hand, you need the cheat codes, then this book will give you a nudge. Redefining the genre of 'self-help comedy,' Shine is a book about the brevity of life. It contains adult themes of mortality, change, exhaustion and unrelenting pressure. Thankfully, the bleakness is done with humour and the solutions are entertaining, do-able and uplifting. Shine is the literary equivalent of 'ctrl/alt/delete.' All you have to do is read the book, keep an open mind, and apply the learning. You will experience a personal re-boot with new mental software installed, upgrading you to 'best possible self.' It's a very simple process that also happens to be 'not very easy.' Because, of course, if being your best self was easy, everybody would be doing it. The average lifespan is 4000 weeks. Look around and you'll see too many people having a 'near life experience.' They're alive, but not living. Truth time: life's a short and precious gift that's hurtling by in a blur. If you want to make a dent in the universe, it's time to wake up. We figure that if you're going to rise, you may as well shine. Laugh and learn while you: Rediscover your ability to ping out of bed every single day with fire in your belly and a smile on your face. Identify what really matters in your life and how to stop stressing about the stuff that doesn't. Remember how to focus on all that makes you happy and cut the nonsense that worries you for no reason. Give up your low-level grumbling and experience the joy that comes when you focus on achieving all that you've ever wanted. Find out just how easy it is boost your energy and increase your motivation. Discover how to break free from 'ordinary' and embrace a life of 'extraordinary.' Figure out how to channel your inner Mary Poppins.